Determination of the striking distance of a lightning rod using finite element analysis - Bakar, Ab Halim Abu; Zainal Abidin, A.; Illias, Hazlee Azil; Mokhlis, Hazlie; Halim, S.A.; Hassan, N.H.N.; Tan, Chia Kwang (Turkiye Klinikleri Journal of Medical Sciences, 2016)
The problems related to electromagnetic waves transmitted by lightning strikes can be studied through physical lightning models based on laboratory results. The main concern of these models is determining the striking distance between the leader tip and the lightning rod during lightning occurrences. The striking distance is a significant factor in designing the lightning protection system. However, models using finite element analysis (FEA) for this purpose are less likely to be found in the literature. Therefore, in this work, a geometry model of a lightning rod and leader was developed using available FEA software. The model was used to determine the striking distance for different lightning rod heights. The results obtained were compared with those of previous research using different methods to validate the models developed using FEA software. From the comparison, the striking distance obtained from the FEA software as a function of lightning rod height was in good agreement compared to other methods from previous research. The use of FEA software also enables the effect of different tip radii of curvature and shapes of the lightning rod on striking distance to be studied, which can further enhance our understanding of the relationship between striking distance and different rod parameters.